THE EFFECT OF MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP, CAPITAL STRUCTURE AND CEO COMPENSATION ON CASH HOLDING - Trisandi Eka Putri; Asep Kurniawan; Anggelya Fitri Romadhona (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
The purpose of this study was to determine the effect for managerial ownership, institutional ownership, capital structure and CEO compensation on the cash holding. This study uses quantitative methods and secondary data from the annual financial statements listed on the Indonesia Stock Exchange. The populations used in this study were the trade, service and investment sectors of companies listed on the Indonesia Stock Exchange for the period 2016-2020. The technique of entering the samples used purposive sampling technique. The analytical tehniqued used was multiple regression analysis with the help of SPSS version 22 program. The results of the study reveal that partially managerial ownership has a negative significant effect on cash holding, capital structure has negative significant effect on cash holding, CEO compensation has a positive significant effect on cash holding, while institutional ownership has no effect on cash holding. As for the simultaneous results that managerial ownership, institutional ownership, capital structure and CEO compensation have an effect on cash holding.